The Effect of Capital on Micro Business Income in Samaturue Village, Tellu Limpoe District, Sinjai Regency - Aditya Anwar Aguswijaya (Income Journal Of Economics Development, 2022)
This study aims to find out the influence of capital on micro-enterprise income in Samaturue Village, Tellu Limpoe District, Sinjai Regency. The type of research used in this research is quantitative research. The data was collected using a questionnaire, observation and documentation methods and then analyzed descriptively and inferentially. The results show that capital has a positive and significant effect on the income of micro enterprises in Samaturue Village, Tellu Limpoe District, Sinjai Regency. This is evidenced from the results of the data in which the regression coefficient value is obtained of 0.270 and a significant value of 0.000 which is less than 0.05.